METODE DAN MODEL PEMBENTUKAN KESIAPAN GURU DALAM PRAKTIK PENDIDIKAN INKLUSI - Wiyanti Maratus Sholihah (PEDAGOGIK : JURNAL PENDIDIKAN, 2020)
The readiness of teachers to teach in inclusive classes is an important key in the implementation of inclusive education. In practice, there are still many teachers who are not ready to teach in inclusive classes. Therefore we need a method or model for developing teacher readiness. The purpose of this study is to conduct a literature review of the methods and models for establishing teacher readiness in the practice of inclusive education. Literature searches were carried out on eight databases, namely ERIC, SpringerLink, ScienceDirect, SAGE, ProQuest, Emerald Insight, Google Scholar and Garuda. Keywords used in literature search are "Teacher Readiness" and "Inclusive Education"; "Teacher Readiness" and "Inclusive School": "Kesiapan guru" dan "Pendidikan Inklusi". A total of 10 articles (N = 1111) will be reviewed through a screening process based on inclusive and exclusive criteria. The results show that the strategy for developing teacher readiness is through training, courses and professional development.